2016
DOI: 10.1371/journal.pone.0150936
|View full text |Cite
|
Sign up to set email alerts
|

CHIR99021 enhances Klf4 Expression through β-Catenin Signaling and miR-7a Regulation in J1 Mouse Embryonic Stem Cells

Abstract: Understanding the mechanisms that regulate pluripotency of embryonic stem cells (ESCs) is important to ensure their safe clinical use. CHIR99021 (CHIR)-induced activation of Wnt/β-catenin signaling promotes self-renewal in mouse ESCs (mESCs). β-catenin functions individually or cooperates with transcription factors to activate stemness factors such as c-Myc, Esrrb, Pou5f1, and Nanog. However the relationship between the core pluripotent factor, Kruppel-like factor 4 (also known as GKLF or EZF) and Wnt/β-cateni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 53 publications
2
15
1
Order By: Relevance
“…40 However, enhancing WNT signaling by blocking the endogenous β-catenin/WNT inhibitor GSK3 reduced atherosclerosis and inflammatory endothelial VCAM-1 expression 41 , further supporting an atheroprotective role of WNT at least partially at the endothelial level. Findings that endothelial KLF4 is itself a β-catenin target gene 42 , drives VE-cadherin expression 43 and is athero­protective in ECs 44 , may provide additional evidence for a down-stream link of CXCL12-induced β-catenin and VE-cadherin expression. Given the involvement of SHP2 in Akt signaling 45 , our data unveil that the CXCL12-CXCR4 axis can sustain endothelial integrity through i) SHP2/Akt/WNT signaling inducing VE-cadherin expression, and ii) VE-cadherin-associated phosphatases, namely VE-PTP, supporting VE-cadherin stability and function.…”
Section: Discussionmentioning
confidence: 99%
“…40 However, enhancing WNT signaling by blocking the endogenous β-catenin/WNT inhibitor GSK3 reduced atherosclerosis and inflammatory endothelial VCAM-1 expression 41 , further supporting an atheroprotective role of WNT at least partially at the endothelial level. Findings that endothelial KLF4 is itself a β-catenin target gene 42 , drives VE-cadherin expression 43 and is athero­protective in ECs 44 , may provide additional evidence for a down-stream link of CXCL12-induced β-catenin and VE-cadherin expression. Given the involvement of SHP2 in Akt signaling 45 , our data unveil that the CXCL12-CXCR4 axis can sustain endothelial integrity through i) SHP2/Akt/WNT signaling inducing VE-cadherin expression, and ii) VE-cadherin-associated phosphatases, namely VE-PTP, supporting VE-cadherin stability and function.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs may sharpen morphogen gradients in the developing embryo or serve as a positive regulator by amplifying signal strength in duration to allow cell responsiveness to subthreshold stimuli (Inui et al, 2010). Recent studies have shown that many miRNAs that are involved in the mitochondrial biogenesis of different cell types are thought to regulate the expression of PGC-1α (Ong et al, 2015;Wu et al, 2015;Ai et al, 2016;Cha et al, 2017;Jiang et al, 2017;Portius et al, 2017;Saini et al, 2018). A study found that CHIR-99021 decreased the mature miRNA levels of most miRNA species in mouse ESCs (Wu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although we assessed that the transcriptional effects of Chiron in absence of β-catenin are negligible, the DGEs in the KOC/WTC comparison were dependent solely on the presence of β-catenin. A similar approach has been used previously [23] by comparing mESCs treated [17][18][19]24]. However, with the exception of a slight Tcfp2l1 upregulation and Dppa3 downregulation, we were not able to identify any change at transcriptional levels of pluripotency marker genes upon Chiron treatment in wild-type cells ( Figure S3C).…”
Section: Canonical Wnt Signalling Inhibits Differentiation Of Mescs Tmentioning
confidence: 58%